Compliment responses in Peninsular Spanish. Exploratory and contrastive study conducted on women from Madrid, Valencia, Catalonia, Andalusia and Castile-Leon - Cuesta, Ana Ramajo (2015)
The aim of the present paper is to examine the influence of the " origin " variable when responding to compliments on physical appearance and belongings in Spain. Participants of the research are female native speakers of Spanish from five Autonomous Communities. Data was gathered by using secret recordings. Results of the research showed that mitigating was the most common compliment response used by women. Despite cultural differences between the Autonomous Communities, no statistically significant results were found.